Talent Management: From Emergence to Development (A Conceptual Study of the Term and Its Dimensions) - Almalki, Sami Hamed (Journal of Educational and Psychological Sciences, 2025)
This study aimed to highlight the nature, importance, and dimensions of talent management, as well as its pivotal role in enhancing competitiveness among institutions—particularly in light of the global race to attract and retain highly skilled human resources capable of meeting institutional needs and achieving organizational objectives. The study employed an inductive approach by reviewing and analyzing existing literature related to the phenomenon under investigation, followed by analytical comparisons of the collected data to derive meaningful conclusions. The findings reveal that talent management represents a developmental extension of human resource management, which in turn evolved from the broader field of management that emerged in the early 20th century and significantly contributed to institutional governance and operational excellence. Although talent management is a relatively recent concept and lacks a universally agreed-upon definition, the researcher defines it as a modern approach aimed at enhancing and refining administrative processes related to human capital. These include recruitment, training, development, retention, and dissemination of talent—ultimately leading to the strategic investment and empowerment of talented individuals to ensure their continued contribution and productivity. This is achieved through mechanisms that integrate talent across various organizational levels within a cohesive framework that ensures synergy among institutional practices—thus reinforcing competitiveness and organizational sustainability. Furthermore, the study underscores the critical importance of talent management in both educational and non-educational institutions. It emphasizes the need to attract talented individuals across disciplines and create environments conducive to innovation and problem-solving. Simultaneously, it advocates leveraging their expertise to deliver competitive products and services that enhance institutional performance and the achievement of strategic goals.
Keywords: Talent Management; Educational Institutions; Human Resources; Leadership; Personal Traits